Analysis of Location and Causes Of College Students' Errors In Probabilistic Problem Solving - Agoestanto, Arief; St. Budi Waluya; Scolastika Mariani; Annisa Salma Zakiyyah (UNNES JOURNAL, 2025)
Problem solving is a necessity for college students, including probabilistic problems. However, student errors in solving these problems continue to occur, necessitating an analysis of the location and causes. The goal of this research is to identify the locations and causes of probabilistic problem-solving errors. This is a qualitative research. The study's subjects were nine students from Semarang State University's Mathematics Education Study Program with low Student Academic Ability (SAA). Based on the subject's problem-solving outcomes, the location and sources of errors in solving probabilistic issues using the Newman Procedure were thoroughly investigated. Data analysis starts with minimising data, then presents data, and finally draws conclusions. Checking the validity of the data using triangulation approaches, such as comparing test results to interview findings and comparing study subjects' outcomes. The findings of this study revealed that the research subjects made errors during the transformation, process skill, and encoding processes. Students' errors are caused by a lack of understanding of the strategy that must be employed in addressing probabilistic problems, topic confusion between the use of permutations and combinations, and confusion in identifying the sample space when taking one or more items in the experiment. The study's findings are likely to inspire and inform lecturers on how to use appropriate learning tactics to limit the possibility of student errors when tackling probabilistic questions. The conclusion of this research is that student errors in probabilistic problem solving lie in the transformation stage, the calculation process , and the error of writing answers so that it is necessary to be given the task of practicing probability problem solving in stages and there are brief instructions in developing a solution strategy. Abstrak Pemecahan masalah sangat penting untuk dikuasai mahasiswa, salah satunya pada masalah probabilistik. Namun, masih sering dijumpai kesalahan mahasiswa dala menyelesaikan masalah tersebut, sehingga perlu dilakukan analisis letak maupun penyebabnya. Penelitian kualitatif ini bertujuan menganalisis letak serta penyebab kesalahan pemecahan masalah probabilistik. Subjek penelitian sebanyak 9 mahasiswa Pendidikan Matematika Universitas Negeri Semarang dengan Kemampuan Akademik Mahasiswa (KAM) rendah. Dari hasil pemecahan masalah subjek dieksplorasi secara mendalam letak dan penyebab kesalahan dalam memecahan masalah probabilistik berdasarkan Prosedur Newman. Analisis data diawali reduksi data, kemudian penyajian data, dan diakhiri dengan penarikan simpulan. Pemeriksaan keabsahan data dengan teknik triangulasi yaitu membandingkan hasil tes dengan hasil wawancara, serta membandingkan hasil subjek-subjek penelitian. Hasil penelitian ini menunjukkan subjek penelitian mengalami kesalahan pada langkah transformation, process skill dan encoding. Adapun penyebab kesalahan adalah tidak mengetahui strategi yang harus digunakan dalam memecahkan masalah probabilistik, subjek kebingungan antara penggunaan permutasi dan kombinasi, kebingungan dalam menentukan ruang sampel antara pengambilan 1 objek dan beberapa objek dalam percobaan. Hasil penelitian ini dapat dijadikan dasar bagi dosen dalam menggunakan strategi pembelajaran yang tepat untuk mengurangi potensi kesalahan mahasiswa dalam menyelesaikan masalah probabilistik. Simpulan dari penelitian ini adalah kesalahan mahasiswa dalam pemecahan masalah probabilistik terletak pada tahap transformasi (transformation), proses perhitungan, dan kesalahan penulisan jawaban sehingga perlu diberi tugas latihan soal-soal pemecahan masalah probabilitas secara bertahap dan terdapat petunjuk singkat dalam menyusun strategi penyelesaian.